Nanomaterials for biogas augmentation towards renewable and sustainable energy production: A critical review - Khan, Sohaib Z.; Zaidi, Asad A.; Naseer, Muhammad Nihal; AlMohamadi, Hamad (Frontiers in Bioengineering and Biotechnology, 2022)
Nanotechnology is considered one of the most significant advancements in science and technology over the last few decades. However, the contemporary use of nanomaterials in bioenergy production is very deficient. This study evaluates the application of nanomaterials for biogas production from different kinds of waste. A state-of-the-art comprehensive review is carried out to elaborate the deployment of different categories of nano-additives (metal oxides, zero-valent metals, various compounds, carbon-based nanomaterials, nano-composites, and nano-ash) in several kinds of biodegradable waste, including cattle manure, wastewater sludge, municipal solid waste, lake sediments, and sanitary landfills. This study discusses the pros and cons of nano-additives on biogas production from the anaerobic digestion process. Several all-inclusive tables are presented to appraise the literature for different nanomaterials used for biogas production from biomass. Future perspectives to increase biogas production via nano-additives are presented, and the conclusion is drawn on the productivity of biogas based on various nanomaterials. A qualitative review of relevant literature published in the last 50 years is conducted using the bibliometric technique for the first time in literature. About 14,000 research articles are included in this analysis, indexed in Web of Science. The analysis revealed that the last decade (2010-20) was the golden era for biogas literature as 84.4% of total publications were published in this timeline. Moreover, it was observed that nanomaterials had revolutionized the field of anaerobic digestion, methane production, and waste-activated sludge; and are currently the central pivot to the research community.